Prognostic Factors for the Failure of Endometrial Ablation: A Systematic Review and Meta-analysis. Issue 6 (December 2019) - Beelen, Pleun; Reinders, Imke M. A.; Scheepers, Wessel F. W.; Herman, Malou C.; Geomini, Peggy M. A. J.; van Kuijk, Sander M. J.; Bongers, Marlies Y.
Abstract : OBJECTIVE: To provide an overview of prognostic factors predicting failure of second-generation endometrial ablation. DATA SOURCES: MEDLINE, EMBASE, the Cochrane Library, and ClinicalTrials.gov were systematically searched from 1988 until February 2019. The search was conducted without language restrictions using the following search terms: "endometrial ablation, " "prognosis, " "predict, " "long term, " "late onset, " "outcome." METHODS OF STUDY SELECTION: The literature search provided a total of 990 studies. All types of studies reporting about prognostic factors of second-generation endometrial ablation failure were included. TABULATION, INTEGRATION, AND RESULTS: After screening for eligibility, 56 studies were included in this review, of which 21 were included in the meta-analysis. In these 56 studies, 157, 830 women were included. We evaluated 10 prognostic factors: age, myomas, history of tubal ligation, body mass index, parity, preexisting dysmenorrhea, caesarean delivery, bleeding pattern, uterus position, and uterus length. Meta-analysis was performed for the primary outcome (surgical reintervention) to estimate summary treatment effects. Younger age (aged 35 years or younger, odds ratio [OR] 1.68, 95% CI 1.19–2.36; aged 40 years or younger, OR 1.58, 95% CI 1.30–1.93; aged 45 years or younger OR 1.63, 95% CI 1.28–2.07), prior tubal ligation (OR 1.46, 95% CI 1.23–1.73), and preexisting dysmenorrhea (OR 2.12, 95% CI 1.41–3.19) were associated with an increased risk of surgical reintervention. Studies investigating the prognostic factors myomas and obesity showed conflicting results. CONCLUSION: Younger age, prior tubal ligation and preexisting dysmenorrhea were found to be associated with failure of endometrial ablation. Obesity and the presence of large submucous myomas may be associated with failure, as well, though more research is necessary to estimate the influence of these factors. It is important to take the results of this review into account when counselling women with heavy menstrual bleeding. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42019126247. Abstract : Younger age, tubal ligation, and dysmenorrhea are associated with endometrial ablation failure, and these factors should be taken into account when counselling women with heavy menstrual bleeding.